The Influence of Fitness Level on Al Qur’an Memorization Ability among UMY UNIRES Students - Permana, Iman; Miftahulhaq; Sabirin, Rahmaningsih Mara; Yuniasih, Dewi (Window of Health : Jurnal Kesehatan, 2024)
One of the activity programs that students at UMY University Residence (UNIRES) must complete within the first year is memorizing Al-Qur'an juz 30. Physical fitness has been linked to good memorization abilities and improving overall cognitive function. More evidence is needed to see how fitness level influences the ability to memorize Al-Qur'an, especially among students. This research aimed to determine the effect of providing an aerobic fitness program on the ability of UNIRES students to memorize Al-Qur'an. The quasi-experimental pre-post test research method without a control group involving 29 participants was conducted; it consisted of 15 male and 14 female residents of UNIRES, who were taken using convenience sampling. The intervention was an aerobic exercise fitness program guided by an instructor, which is carried out every two days for 30 minutes for 14 days and can be followed independently via the YouTube link provided. The fitness test is carried out using the 6-minute walk test method, given before and after students are given aerobic treatment and determined by measuring VO2 max. Participants were asked to memorize Al-Qur'an Surah An Nisaa verse 23 and measured the duration of memorization. This verse was chosen because of the trickiness and complexity level of the words; there are several similar words/sentences repeated (words ending in تُكُمْ) in the verse. The average VO2 max before and after intervention was 40.97 ± 9.87 and 42.68 ± 5.00, while memorization ability was 2,496.21 ± 1,654.53 seconds and 1,162.62 ± 726.33 seconds. There was no significant difference in VO2max before and after training with p 0.508, greater than 0.05. Conclusion: No significant correlation exists between memorization time and VO2max, either before or after training. The interventions need to be extended to get more optimal results, and the number of participants needs to be increased, besides the involvement of a control group.